Cultural modes of conflict resolution, roommate satisfaction, and school belonging: The role of socioeconomic status in university peer relations - Rocio Burgos-Calvillo; Yolanda Vasquez-Salgado; Patricia M. Greenfield (Current Research in Ecological and Social Psychology)
It is often assumed that ethnic differences are the source of cross-cultural conflict and misunderstandings in the United States. However, research indicates that socioeconomic differences, i.e., family ecologies, play an important role in producing cross-cultural value conflict between student peers in a university setting. Our prior research revealed two resolution styles: (1) a collectivistic strategy – maintaining interpersonal harmony by avoidance or implicit communication, or (2) an individualistic strategy – advocating for and expressing one's personal feelings via explicit communication. In a small qualitative study of first-generation university students from Latin American immigrant families, improved roommate relations resulted from use of the more individualistic strategy. The purpose of the present study was to extend this work by examining whether the positive role of explicit conflict resolution with dormitory roommates generalizes to a large diverse sample of university students in the United States and to examine the role of socioeconomic status, a key aspect of the ecological surround. By means of a survey of 347 first-year UCLA students, we explored the interrelations of socioeconomic status, conflict resolution style, roommate relations, sense of belonging in the university environment, and psychological distress. Socioeconomic status consisted of parent education and income, which were closely related. Being a first-generation university student (i.e., neither parent had a postsecondary degree) was, as predicted, associated with harmony-maintaining modes of resolving roommate conflicts. In accord with our earlier qualitative findings, these modes of conflict resolution were less effective than an explicit mode in producing satisfying roommate relations. Less satisfying roommate relations led, in turn, to a lower sense of belonging in the university environment and more psychological distress. This causal chain from first-generation university status to less satisfying roommate relations, a lower sense of belonging, and more psychological distress may help explain the prevalence of ''imposter'' syndrome among first-generation university students.